Treatment Outcome of Malnourished Patients with Respiratory Tract Infections - Rafique, Rubina (International Journal of Pathology, 2019)
Introduction: Malnutrition is associated with negative outcomes for patients, including higher infection and complication rates, increased muscle loss, impaired wound healing, longer length of hospital stay and increased morbidity and mortality. The negative effect of malnutrition on respiratory infection and muscle strength has also been established. Therefore, this study was designed to find out the treatment outcomes of malnourished acute respiratory infection (ARI) patients. Objective: To observe the relation between the poor nutritional status & outcome of patients Materials & Methods: In this study there were 23(44.2%) male and 29(55.8%) female cases while 27(51.9%) cases were in 16-35 years of age, 7(13.5%) cases were 35-45 years old and 18(34.6%) cases were 45-65 years old. This observational & prospectivestudy was conducted atSKBZ/CMH Muzaffarabad Azad Kashmir.All patients who fulfilled inclusion criteria were included consecutively. All cases with age 16-65 years of either gender were included. Treatment outcome was labelled as good or bad. Mean and standard deviations were calculated for quantitative variables and frequency and percentages were calculated for qualitative variables. Results: A total of 42(80.8%) cases had length of hospital stay for 1-7 days, 9(17.3%) cases had 8-14 days and 1(1.9%) cases had ≥ 14 days. According to final outcome 17(32.7%) cases had bad and 35(67.3%) cases had good outcome. Moreover, 34(65.4%) cases had improved, 2(3.8%) cases were referred or left against medical advice and 16(30.8%) remained in follow up. Conclusion: Malnutrition remains a burden for general healthcare and has considerable impact on worsening the treatment outcome of ARI in malnourished patients.